2019
DOI: 10.1021/acsomega.9b03342
|View full text |Cite
|
Sign up to set email alerts
|

Electroreductive Intermolecular Coupling of 4-Quinolones with Benzophenones: Synthesis of 2-Substituted 4-Quinolones

Abstract: The electroreductive coupling of 1-alkoxycarbonyl-4-quinolones with benzophenones in the presence of trimethylsilyl chloride gave adducts reacted at the 2-position of 4-quinolones as trimethylsilyl ethers. The adducts were transformed to 2-(diarylhydroxymethyl)-4-quinolones. The electroreduction of 1,3-diethoxycarbonyl-4-quinolones and polyhalogenated 3-alkoxycarbonyl-1-alkyl-4-quinolones with benzophenones also gave adducts reacted at the 2-position of 4-quinolones. On the contrary, the electroreductive coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…[22] The traditional nucleophilic reactions can be replaced by a promising alternative using highly reactive organometallic reagents such as Grignard reagents is by employing a mild electrochemical approach to generate ketyl radicals/anions for subsequent addition or crosscoupling. [22] In 2019, for instance, Kise and co-workers carried out a two-electron cathodic reduction of diaryl ketones using trimethylsilyl chloride (TMSCl) to hydrofunctionalize chromones [24] and 4-quinolones; [25] the TMS-protected alcohols or similar compounds thus formed are found to be capable of undergoing further different transformations to attain various functionalized structures.…”
Section: Reductive Functionalization Of C=o Bondmentioning
confidence: 99%
“…[22] The traditional nucleophilic reactions can be replaced by a promising alternative using highly reactive organometallic reagents such as Grignard reagents is by employing a mild electrochemical approach to generate ketyl radicals/anions for subsequent addition or crosscoupling. [22] In 2019, for instance, Kise and co-workers carried out a two-electron cathodic reduction of diaryl ketones using trimethylsilyl chloride (TMSCl) to hydrofunctionalize chromones [24] and 4-quinolones; [25] the TMS-protected alcohols or similar compounds thus formed are found to be capable of undergoing further different transformations to attain various functionalized structures.…”
Section: Reductive Functionalization Of C=o Bondmentioning
confidence: 99%
“…Interestingly, the functionalization of 3-methylchromone and 3-arylchromone produced selectively the cis -adducts (Scheme ). Soon after, the authors extended this procedure to the C2-functionalizations of 4-quinolones …”
Section: C­(sp3)–c­(sp3) Bond Formationmentioning
confidence: 99%
“…Soon after, the authors extended this procedure to the C2-functionalizations of 4-quinolones. 32 Baran and Minteer et al reported an electroreductive coupling between aliphatic ketones 61 and unactivated alkenes 62 for the synthesis of tertiary alcohols 63 in good yields. 33 The electrolysis was performed in an undivided cell using a zinc-based sacrificial anode and tin cathode.…”
Section: Set Reduction Of Ketonesmentioning
confidence: 99%